2013
DOI: 10.1016/j.bbadis.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP21 is a RhoGAP for RhoA and RhoC with a role in proliferation and migration of prostate adenocarcinoma cells

Abstract: Our results reveal new functions and signaling pathways regulated by ARHGAP21, and indicate that it could contribute to prostate cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 57 publications
2
72
0
3
Order By: Relevance
“…Cellular Context, How the RHOGAPs Determine and Regulate Specificity-Several cell-based studies have shown that there is specificity between RHOGAP and RHO proteins as follows: ARHGAP15, BCR, ␤-chimaerin, 3BP1, p68RACGAP, and FILGAP are specific for RAC1 (29, 50 -54); RALBP1 and MGCRACGAP1 are specific for both CDC42 and RAC1 (55-57); RICH1 and CDGAP are specific for CDC42 (58, 59); ARHGAP6, DLC1, DLC3, myosin IXb, OPHN1, p190A, and RA-RHOGAP are specific for RHOA (34, 47, 60 -68); ARHGAP18, ARHGAP21, and DLC1 are specific for RHOC (64,66,69); TCGAP is specific for TC10 (70); PARG1 is specific for RHOA (71), and ARHGAP30 is specific for WRCH1 (72).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular Context, How the RHOGAPs Determine and Regulate Specificity-Several cell-based studies have shown that there is specificity between RHOGAP and RHO proteins as follows: ARHGAP15, BCR, ␤-chimaerin, 3BP1, p68RACGAP, and FILGAP are specific for RAC1 (29, 50 -54); RALBP1 and MGCRACGAP1 are specific for both CDC42 and RAC1 (55-57); RICH1 and CDGAP are specific for CDC42 (58, 59); ARHGAP6, DLC1, DLC3, myosin IXb, OPHN1, p190A, and RA-RHOGAP are specific for RHOA (34, 47, 60 -68); ARHGAP18, ARHGAP21, and DLC1 are specific for RHOC (64,66,69); TCGAP is specific for TC10 (70); PARG1 is specific for RHOA (71), and ARHGAP30 is specific for WRCH1 (72).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ARHGAP21 was identified as a potential tumor suppressor, being able to control the progression of the disease. ARHGAP21 depletion was also found to increase cell migration and decrease proliferation in prostate adenocarcinoma cell line (PC3) (Lazarini et al, ). The increase in migration was attributed to its RhoGAP action over RhoC, as the lack of ARHGAP21 resulted in increased RhoC activity, which in turn led to increased migration (Lazarini et al, ).…”
Section: Arhgap As a Regulator Of Cytoskeletal Processes In Cancer Cellsmentioning
confidence: 99%
“…They play a role in the migration, invasion and proliferation of tumor cells by affectting cell movement and adhesion in the cell-cell or cell-matrix, and the reconstruction of the extracellular matrix (5,6). Rho subfamily members play an important role in the migration, invasion and proliferation of tumor cells, while the behavior of the embryo implanted in the endometrium is similar with the behavior of tumor cells (7).…”
Section: Introductionmentioning
confidence: 99%